KEARIFAN MASYARAKAT LOKAL DALAM PENGELOLAAN HUTAN DI DESA RANO KECAMATAN BALAESANG TANJUNG KABUPATEN DONGGALA - Ariyanto, Ariyanto; Rachman, Imran; Toknok, Bau (Jurnal Warta Rimba, 2014)
The local wisdom is a knowledge obtained in hereditary that becomes a custom and based on the values and based on the values and norms of society. As the To`Balaesan ethnic or the original ethnic in Rano village inhibiting Tanjung Balaesang cluster lies on viscous culture covering language, religion system, and a little different physics from the other society in the area of Balaesang Tanjung sub district. The method employed was explorative descriptive with a qualitative approach through the exploration of key informants information. Thus it can describe a certain situation or a group of human systematically, factually, and accurately based on the fact in the field. The data were collected through observation and interview with a good structured guidance or free interview. The population was the Rano people. The selection of the informants was by using snow-ball sampling. The result indicates that Rano people still uphold their tradition they know from the past, seen from the land selection process, land opening and the farming process. All of it accumulated in a topomaradia tradition institution which contains a set of rules and inferences as the attitude manager norms and behavior of the ethnic society to`balaesang in Rano village. Key words: Local Wisdom, ethnic of ta`Balaesan, Rano Village